PERAN HUKUM PIDANA BAGI ANAK SEBAGAI PELAKU PERAMPOKAN (BEGAL) - Yusuf Hanafi Pasaribu (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Discussions about children and their protection will never stop throughout the history of life, because children are the next generation of the nation and the successors of development, namely the generation that is prepared as the subject of implementing sustainable development and the future controllers of a country, not least in Indonesia. Child protection in Indonesia means protecting the potential of human resources and building Indonesian human beings as a whole, towards a just and prosperous society, materially and spiritually based on Pancasila and the 1945 Constitution.In positive law in Indonesia, the issue of minors regarding when they commit illegal acts, is not so firmly regulated; what should be treated for them, and how the detention system and the investigation system given to them are also not yet regulated in law.